Continuous Pharmaceutical Manufacturing - Ossi Korhonen (Pharmaceutics, 2020)
Pharmaceutical manufacturing is facing the greatest ideological revolution since industrial drug manufacturing. Drugs have been traditionally manufactured in batch mode, but now, continuous manufacturing has started to gain serious interest in the pharmaceutical industry. [...]